Technical efficiency analysis of harumanis mango production under contract farming in Perlis / Farah Habibah Md. Zain - Md. Zain, Farah Habibah (2021)
Harumanis mango is the most common mango clone that has been registered as MA 128 under the Department of Agricultural, Malaysia (DOA) among all mango varieties in Malaysia. It was assumed that Harumanis is originated from Indonesia and was domesticated in Malaysia since it was legally registered with DOA on May 28, 1971. Contract farming is one of the large projects that are launched as a mechanism to help small and medium-scale agricultural production farmers to guarantee their agricultural produce returns that match with their effort. The main factor of growth is due to the efficiency in resources and technology use. However, there is still not much study has been carried out in on the technical efficiency of Harumanis mango in Perlis, Malaysia especially in term of technical efficiency. The aims of the study are to examine the technical efficiency among the selected Harumanis mango farms and to identify the socioeconomic factors that influence the technical efficiency of Harumanis mango farms in Perlis. A convenience sampling method was used to collect the data through the distribution of questionnaire and directly interview farmer to get a further information. In this study, about 30 sample size is used to collect the data of Harumanis mango production by selecting the respondents from 216 of total population of Harumanis mango farmer among the whole contract farmers under Federal Agricultural Marketing Authority (FAMA), Perlis. There are two methods used to conduct the technical efficiency and determinant factors by the Data Envelopment Analysis (DEA) and Tobit Regression Analysis respectively. Based on the findings, age and agricultural extension positively influenced the technical efficiency and only age of farmer is show significant result. In conclusion, age, educational level and agricultural extension is one of the factor that impact the technical efficiency of Harumanis mango in Perlis, Malaysia. If the technical efficiency factor of Harumanis mango plantation is control, introduced other initiatives or used a improvement technology that had been introduced by any agricultural agencies or adopt a technique and technology used from other country such as Japan and Indonesia, we may have an opportunity to increase the production and the quality of Harumanis mango in the future. Based on recommendation, research in plantation need to do a lot of research regarding the technical efficiency of Harumanis mango in Perlis and they also need to include the study about the agricultural education from the farmer status instead only depend on the general education of the farmers.